BIOLOGICAL FLUID VISCOSITY: PHYSIOLOGICAL BASIS, DETERMINANTS AND CLINICAL SIGNIFICANCE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Viscosity is a key physical property of biological fluids that determines their resistance to flowand directly influences circulation, tissue perfusion, and cellular transport. This article provides anin-depth analysis of the viscosity of biological fluids—primarily blood—integrating principles offluid mechanics with physiological and clinical perspectives. The determinants of viscosity,including hematocrit, plasma protein concentration, temperature, and shear rate, are discussedalongside their role in normal physiology and disease states. Alterations in viscosity are shown toplay a critical role in cardiovascular disorders, diabetes mellitus, and inflammatory conditions,making it an important diagnostic and prognostic parameter in modern medicine